Determining the effect of the ratio of tryptophan to large neutral amino acids on the growth performance of finishing pigs - Nitikanchana, S.; Usry, J.L.; Bergstrom, J.R.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 96 pigs (PIC TR4 × 1050; initially 77.4 lb) were used in 2 14-d studies to determine the effect of standardized ileal digestible (SID) tryptophan to large neutral amino acids (LNAA) ratio on growth performance of finishing pigs. Pens of pigs were balanced by initial weight and randomly allotted to 1 of 4 dietary treatments in a completely randomized design with 4 pigs per pen and 6 replications per treatment. The treatment diets were fed in 2 phases: early finishing phase (77 to 106 lb BW) and late finishing phase (183 to 217 lb BW), with a common diet fed in between. Dietary treatments included: (1) a corn-soybean meal-based diet without DDGS, (2) a cornsoybean meal-based diet with 45% dried distillers grains with solubles (DDGS), (3) a corn-soybean meal-based diet without DDGS but supplemented with similar amounts of LNAA as the diet containing 45% DDGS, and (4) the LNAA-supplemented diet with added crystalline tryptophan to increase the SID tryptophan:LNAA ratio. The diets were formulated in a similar manner for the late finishing phase with the exception that DDGS were lowered to 30% of the diet. In the early finishing period (77 to 106 lb), pigs fed 45% DDGS diet had poorer F/G (P = 0.01) compared with pigs fed the other diets; however, no differences were found in other response criteria. During the late finishing period (183 to 217 lb), pig growth performance was not affected by dietary treatment. These results suggest that the high level of LNAA relative to trypto- phan in diets containing 30% DDGS or greater may not be responsible for the apparent increase in the tryptophan requirement of finishing pigs seen in previous studies.
Keywords: Swine; Amino acids; Large neutral amino acids; Lysine; Tryptophan; Finishing pig